MOVE STRUCTURES AND THEIR RHETORICAL VERBS OF RESEARCH ARTICLE ABSTRACTS ACROSS ENGLISHES - Tocalo, Abdul Wahid Ibrahim (Universitas Pendidikan Indonesia, 2021)
Genre-based studies on moves structure of research article (RA) abstracts have established variations across cultures. However, previous studies included at most two countries for comparisons of abstracts written by native against non-native speakers. With the advent of World Englishes, it is deemed more practical to examine abstracts across Englishes to determine the writing conventions of the L1, L2 and EFL speakers of English. Consequently, the present study is a structural move analysis of RA abstracts focusing on the macro-structural moves across the Englishes and the lexical verbs employed used in each move. It examined 36 RA abstracts from linguistics and language and education fields, consisting of 12 abstracts each from the Inner, Outer and Expanding Circles of English by Kachru (1992). Each abstract was segmented into moves using the Five-Move Model of Santos (1996), which includes moves: (1) Situating the Research (STR); (2) Presenting the Research (PTR); (3) Discussing the Methodology (DTM); (4) Summarizing the Findings, (STF), and (5) Discussing the Research (DTR). The study found that the Inner Circle of English has the structure: Abstract Ã (STR) + PTR + DTM + (STF) + (DTR). The Outer Circle has the structure: Abstract Ã (STR) + PTR + (DTM) + STF + DTR. The Expanding Circle has the structure: Abstract Ã (STR) + PTR + DTM + (STF) + (DTR). The formulaic structures of abstract moves revealed that the only common move across Englishes is PTR. Following the approach of Musa et al. (2015), the lexical verbs realizing the purpose of each of the rhetorical moves were listed in order to come up with lists of rhetorical verbs which can be used in structuring an RA abstract. The study concludes with implications for academic writing instruction that calls for future abstract analyses that are world Englishes-inspired.